The Role Of Digital Transformation In Accounting Systems For The Transparency And Accountability Of Msme Financial Statements - Wistiani Zebua (Interdisciplinary Social Studies, 2025)
This study aims to analyze the role of digital transformation in the accounting system on the transparency and accountability of financial statements in Micro, Small, and Medium Enterprises (MSMEs). Digital transformation includes the use of technologies such as cloud-based record-keeping, transaction automation, and accounting applications that support real-time and accountable financial record-keeping. The results show that digital transformation has a significant positive effect on transparency with a coefficient of 0.876 and on accountability of 0.737. The R-square value of 76.7% for transparency and 54.4% for accountability shows the strong contribution of digital transformation to both variables. This research provides practical implications for MSMEs to improve financial governance through the application of digital technology.